The Effect of Pocket Books as Nutrition Counseling Media on Knowledge and Attitudes of Prospective Bride and Groom - Arvina Dian Wahyu Permatasari (Green Publisher Indonesia, 2022)
The First Thousand Days of Life or 1000 HPK (Golden Period) is a critical period starting from conception until the child is 2 years old. Bride and groom are one of the target groups to improve health quality in 1000 HPK. Improving the quality of health can be done by providing pocket books as a medium for nutritional counseling. This research aims to determine the effect of pocket books as a medium for nutritional counseling on the knowledge and attitudes of prospective brides and grooms. This research uses the method true experiment research with randomized pre and posttest control group design. The number of respondents was 36 brides and grooms who registered at the Pedurungan Office of Religious Affairs (KUA) of Semarang City, which consisted of 19 interventions (given counseling and pocket books) and 17 controls (only counseled). Knowledge and attitude data were collected using a questionnaire. The test used to determine the effect between variables is the Paired Sample T-test. Results: There was an effect of pocket books as a medium of nutrition counseling on knowledge in the intervention group (p=0.000) and control (p=0.000) and intervention attitude (p=0.000), but there was no effect on control attitudes (p=0.438). Knowledge of respondents in the intervention group increased by 10.26 while attitudes increased by 11.32. This study concludes that the provision of pocket books as a medium for nutritional counseling has an effect on increasing the knowledge and attitudes of the bride and groom.